The rational conducting of pregnancy and kinds with the immunological conflikt (experience of 35-years work) - G. M. Pertseva; A. A. Borsheva; Э. E. Kudinova (Медицинский вестник Юга России, 2011)
Purpose: To estimate efficiency of work of the specialized reception of pregnant with an immunological conflict.Materials and Methods: The analysis of flow of pregnancy is conducted, births, ends for a fruit in 5- ti clinical groups. A dynamic supervision was conducted, a title was determined groups and anti-rezusnykh antibodies, ULTRASONIC, dopplerometriya fruit.Results: In all 21659 children borned in all clinical groups, at the 1377 (6,4%) new-born was GB is diagnosed.Summary: The got results confirmed efficiency of work of the specialized reception, that allowed to reduce morbidity ot gemoliticheskoy illness in 6 times.